2018
DOI: 10.1177/1461444818772063
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on the dark social: The connective role of news and journalism in social media communities

Abstract: Messaging apps and Facebook groups are increasingly significant in everyday life, shaping not only interpersonal communication but also how people orient themselves to public life. These "dark social media" are important spaces for "public connection," a means for bridging people's private worlds and everything beyond. This article analyzes how people perceive news on such platforms, focusing on the different roles it plays in key social networks that rely on dark social media for communication. Arguing that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 47 publications
0
28
0
5
Order By: Relevance
“…From social media feeds where news and personal updates interweave in a virtual environment based on algorithmic personalization (Bruns, 2017), to the continued growth of smartphones as a media device (Newman et al, 2018), to the gradual emergence of "dark" social media platforms (i.e. messaging apps) to discuss public affairs (Swart, Peters & Broersma, 2018), how people are socialized to see, share, and talk about news is undergoing a radical transformation. The individualization of media devices, fragmentation of outlets, and personalization of consumption increasingly renders news use a personally-visible, but publicly-invisible practice.…”
Section: News Repertoiresmentioning
confidence: 99%
See 1 more Smart Citation
“…From social media feeds where news and personal updates interweave in a virtual environment based on algorithmic personalization (Bruns, 2017), to the continued growth of smartphones as a media device (Newman et al, 2018), to the gradual emergence of "dark" social media platforms (i.e. messaging apps) to discuss public affairs (Swart, Peters & Broersma, 2018), how people are socialized to see, share, and talk about news is undergoing a radical transformation. The individualization of media devices, fragmentation of outlets, and personalization of consumption increasingly renders news use a personally-visible, but publicly-invisible practice.…”
Section: News Repertoiresmentioning
confidence: 99%
“…Tentatively, we may say that a news repertoire changes when one or more of these considerations underlying the worthwhileness balance causes the repertoire to "recompose". To go back to the exemplar raised in the introduction, recent qualitative (Swart, Peters & Broersma, 2018) and quantitative (Newman et al, 2018: 12) studies have shown that "dark" social media platforms are becoming increasingly popular to share and discuss news, with people finding they "offer more convenience, greater privacy, and less opportunity to be misunderstood." In this way, new media alternatives sometimes act as replacements while other times they are complementary.…”
mentioning
confidence: 99%
“…This is the kind of engagement that affects people, that perhaps changes views and behaviours and therefore has democratic impact. This kind of engagement can manifest itself as technical engagement, but-as audience research has clearly shown (e.g., Swart, Peters, and Broersma 2018; Ytre-Arne and Moe 2018)-quite often it does not. The perhaps somewhat banal but nonetheless crucial point is that people can be emotionally engaged with news even if they do not participate in it by creating content, commenting, sharing or liking news stories online.…”
Section: What Is Audience Engagement?mentioning
confidence: 99%
“…Feminism saw the Internet as an opportunity for freedom, emancipation and equality (Colley and Maltby, 2008; Haraway, 1998; Plant, 1997), as a safe space (Clark-Parsons, 2018), its control and privacy (Swart et al, 2018) even though it was aware of structural limitations such as access, cost, literacy and sexism (Eudey, 2012). This is why some feminist theorists (De Miguel and Boix, 2002; Mohanty and Samantaray, 2017) conclude that cyberfeminism is one of the keys to a new social and economic order, one in which the role of women is constructively redefined.…”
Section: Technology and Social Movements: Cyberfeminismmentioning
confidence: 99%